Cyberterrorism: the legal and enforcement issues - Pardis Moslemzadeh Tehrani (World Scientific, 2017)
Definitional issues relating to cyberterrorism -- The challenges faced by international organizations in curbing cyberterrorism -- Application of legal provision in the case of cyberterrorism -- Issues of enforcement in cyberterrorism -- Issues of jurisdiction for cyberterrorism -- Conclusion and recommendations